Rancang Bangun Sistem Informasi Administrasi Klinik Berbasis Website Menggunakan Metode Extreme Programming - Yosep Septiana; Wiyoga Baswardono; Rosy Elisa Nurkholis Awaludin (Jurnal Algoritma, 2022)
The existence of health institutions that provide health services today is growing not only in hospitals, but also in clinics. One of the clinics that distributes health services is the Baiturrahman Clinic which is located on Jalan. Merdeka Number. 217, Jayaraga, Tarogong Kidul District, Garut Regency, West Java 44151. Baiturrahman Clinic certainly provides basic and specialized medical services, with health workers who are self-perpetuating and have knowledge and expertise in the health sector. Not only that, patient satisfaction is also one of the most important aspects that make health service activities run dynamically, especially in clinical administration services, especially for inpatients, this clinic still does not use data technology in carrying out maximum services, there are still many patients who do not know data regarding inpatient treatment costs in totality, thus causing the patient or the patient's family to find out about payment data for clinical administration staff. Therefore the purpose of this research is to design a web-based clinical administration data system. The methodology used is Extreme Programming (XP) which has several stages, namely planning, design, coding, and testing. The procedure for testing uses black box testing. The results of this research are in the form of a clinical administration data system that can make it easier to search for data regarding inpatient healing fees in totality even remotely.